A bioreactor system for interfacial culture and physiological perfusion of vascularized tissue equivalents. Issue 3 (9th November 2012) - Groeber, Florian; Kahlig, Alexander; Loff, Steffan; Walles, Heike; Hansmann, Jan
Abstract A pivotal requirement for the generation of vascularized tissue equivalents is the development of culture systems that provide a physiological perfusion of the vasculature and tissue‐specific culture conditions. Here, we present a bioreactor system that is suitable to culture vascularized tissue equivalents covered with culture media and at the air–medium interface, which is a vital stimulus for skin tissue. For the perfusion of the vascular system a new method was integrated into the bioreactor system that creates a physiological pulsatile medium flow between 80 and 120 mmHg to the arterial inflow of the equivalent's vascular system. Human dermal microvascular endothelial cells (hDMECs) were injected into the vascular system of a biological vascularized scaffold based on a decellularized porcine jejunal segment and cultured in the bioreactor system for 14 days. Histological analysis and 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) staining revealed that the hDMECs were able to recolonize the perfused vascular structures and expressed endothelial cell specific markers such as platelet endothelial cell adhesion molecule and von Willebrand factor. These results indicate that our bioreactor system can serve as a platform technology to generate advanced bioartificial tissues with a functional vasculature for future clinical applications.